Evaluation of Growth Differentiation Factor-15 in Patients with or without Coronary Artery Disease: Growth Differentiation Factor-15 in Coronary Artery Disease - Hassanzadeh Daloee, Shima; Nakhaei, Nima; Hassanzadeh Daloee, Mahdy; Mahmoodi, Mahmood; Barzegar-Amini, Maral (Acta Biomedica Atenei Parmensis, 2021)
Background: Growth-differentiation factor-15 (GDF-15) is a distant member of the transforming growth factor-beta cytokine superfamily expressed in human atherosclerotic plaque macrophages. In this study, we sought to compare GDF-15 between patients with coronary artery disease and control group.Methods: In this cross-sectional study, 176 subjects were enrolled, consisted of 88 coronary artery disease patients (CAD group) and 88 non-CAD participants (control group. Clinical and demographic data, comprising of family history of CAD, history, and lifestyle factors, hypertension, diabetes, and some blood parameters (e.g. glucose, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C)), triglyceride, high-sensitivity C-reactive protein (hs-CRP)).Results: Mean age of the patients was 55.5±11.1 years (age range: 28–80 years). Of all the participants, 91 (51.7%) were male and 85 (48.3%) female. Hs-CRP, LDL-C, and GDF-15 levels were significantly higher in the CAD patients (P=0.091, P=0.008, and P